2016
DOI: 10.1093/bja/aew174
|View full text |Cite
|
Sign up to set email alerts
|

Surgicric 2: A comparative bench study with two established emergency cricothyroidotomy techniques in a porcine model

Abstract: This study supports training in and the use of surgical cricothyroidotomy by anaesthetists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…Although there was an added step of inserting the introducer following scalpel incision, the insertion times were significantly faster in this simulated obese model. However, the times taken in this study was longer and required more insertion attempts compared with the cricothyroidotomy studies previously conducted in our institution on a similar porcine model, but with only a thin overlying layer of skin. This correlates with the knowledge that cricothyroidotomy is technically more challenging and demanding in obese subjects, as observed in a previous simulated obese neck study .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although there was an added step of inserting the introducer following scalpel incision, the insertion times were significantly faster in this simulated obese model. However, the times taken in this study was longer and required more insertion attempts compared with the cricothyroidotomy studies previously conducted in our institution on a similar porcine model, but with only a thin overlying layer of skin. This correlates with the knowledge that cricothyroidotomy is technically more challenging and demanding in obese subjects, as observed in a previous simulated obese neck study .…”
Section: Discussionmentioning
confidence: 78%
“…We calculated that we would need a sample size of at least 25 participants to show whether the insertion times for a pair of devices differed by more than a threshold value of 45 s and standard deviation of difference of around 80, using a two‐sided, 5% significance level and 80%, based on two studies comparing cricothyroidotomy techniques conducted in our institution . We used the Wilcoxon matched pairs signed‐rank test to analyse the results (non‐normal distributions) and the McNemar test to compare the success rate, occurrence of false passage and identification of cricothyroid membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The study power calculations were performed based on cricothyroidotomy procedural time. Based on a similar study [8], we derived the standard deviation of 29 s. To demonstrate a difference of 20 s as described in our previous work [9], for a power of 0.9, with a significance level of 0.05, 50 participants were needed in each group. The differences in procedural times and heart rates were analysed using the paired Student t-test.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using cadavers and animal models have shown that, compared with percutaneous cricothyrotomy (with Seldinger or Trocar method), surgical cricothyrotomy was associated with a higher success rate and a lower incidence of complications [38,39]. Because of these reasons, it is now recommended that surgical cricothyrotomy should be regarded as the most reliable method, and should be learned and regularly rehearsed by all anesthesiologists [4,40].…”
Section: 'Rescue Device'mentioning
confidence: 99%